Quality control standardization of Blumea lacera (Burm.f.) DC. Leaves - Dubey, Tarkeshwar; Bhanukiran, Kancharla; Hemalatha, Siva (Indian Journal of Natural Products, 2019)
Background: Blumea lacera (Burm.f.) DC.(Asteraceae) is one of the annual herb indigenous to plains of North-west India, Tropical Africa and South East Asia. Hypothesis:Despite the popular exploitation of this herb as medicine, still no proper study has been reported regarding the pharmacognostical standardization of its leaves. Thus, the aim of the present study was to scientifically establish a standard monograph based on pharmacognostical and phytochemical aspects as per World Health Organization guidelines. Method: The diagnostic characters of the Blumea lacera (Burm.f.) DC. Leaves were evaluated based on the macroscopical and microscopical characters. Heavy metal content, microbial load assesment, fluorescence drug analysis and preliminary phytochemical screening of different fractions were also carried out. Results: Determination of various physicochemical parameters such as total ash (23.412% w/w), water soluble ash (1.615% w/w), acid insoluble ash (14.625% w/w), alcohol soluble extractive (8.28% w/w), water soluble extractive (19.56% w/w), hexane soluble extractive (2.3% w/w), loss on drying (17.533 % w/w) and crude fibre content (2.75% w/w) were ascertained.Total phenols (367.4779±7.83 mg/g gallic acid equivalent), tannins (29.039±1.109 mg/g tannic acid equivalent), flavonoids (244.751±3.003 mg/g rutin equivalent, RE), flavonols (48.284±1.465 mg/g RE) and, total alkaloidal content (25.56±1.926 mg/g atropine equivalent) were quantified from the ethanolic extract of the leaves of Blumea lacera (Burm.f.) DC.(EBL).Quantification of quercetin in the EBLwas assessed by HPLC analysis and was found to contain 31.603±1.141 mg/g. Conclusion: The obtained qualitative and quantitative standards will provides referential information for correct identification and standardization of this medicinal plant.
Keywords: Blumea lacera (Burm.f.) DC; pharmacognosy; quercetin; HPLC